A rare case of tuberculoma masquerading as CP Angle neoplasm - Ghosh, Sinjan; Guha, Gautam; Roy, Kaushik; Bhattacharjee, Annesh; Repaka, Nikhil; Nanda, Sourav; Agasti, Niraja (Asian Journal of Medical Sciences, 2019)
Tuberculoma involving the cerebellopontine angle is very rare. Preoperative neuroradiological features of such lesions may mimic neoplastic lesions. Our case presented with cerebellar features and multiple cranial nerve palsy. Neuroimaging mimicked CP angle neoplastic lesion. Antitubercular therapy and steroids resulted in significant clinical improvement and marked radiological reduction in size of the lesion. In our subcontinent a treatable infective cause like tuberculosis should be ruled out in CP angle lesions. Although rare but definitely a possibility to be considered.